APPLICATION OF MODERN EDUCATIONAL TECHNOLOGIES IN TEACHING SOIL SCIENCE AND AGROCHEMISTRY (Scientific journal of the Fergana State University, 2025)
The article describes modern educational technologies and their application, which should be used in the training of highly qualified soil scientists and agrochemists in the higher education system.